Impact of Emotional Intelligence on Knowledge Sharing and Knowledge Hiding Behavior - Nadra Mahmood; Alpaslan Toker (Eurasian Journal of Management & Social Sciences)
During the last few decades, researchers have proven that controlling and sharing employee knowledge is critical for effective organizational transformation, innovation, and competitive advantage. Despite various efforts to promote information sharing inside businesses, individuals may not always be willing to share the knowledge assigned to them due to personal views or environmental restrictions that lead to knowledge concealment. We looked at the impact of emotional intelligence (EI) on knowledge sharing (KS) and knowledge hiding (KH). We collected 149 data points from various firms in Iraq to examine this effect. As a result, we discovered a positive impact on emotional intelligence and knowledge sharing and concealment. employees who understand their feelings and other feelings will tend to share their knowledge of the things that they want to share their knowledge and it will impact the company positively to increase creativity, innovation, teamwork, increasing productivity of the firm, but on the other hand, employees who do not fully understand their feelings and other feelings they will lean on hiding knowledge of their own and to conceal most parts. Therefore, in literature, it will affect the company negatively (creating problems, lack of knowledge).